2018
DOI: 10.1089/cbr.2017.2254
|View full text |Cite
|
Sign up to set email alerts
|

PTPN12 Affects Nasopharyngeal Carcinoma Cell Proliferation and Migration Through Regulating EGFR

Abstract: PTPN12 regulates NPC proliferation and migration through negative regulating EGFR. It could be treated as a molecular target for NPC diagnosis and prognosis analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…PTPN12, is a member of the Protein tyrosine phosphatases family (48) and is frequently downregulated in several types of human cancer, including nasopharyngeal carcinoma (28), ovarian cancer (49), breast cancer (50) and hepatocellular carcinoma (51). PTPN12 serves as a tumor-suppressor in cancer initiation and progression by regulating a wide range of biological processes, including cell proliferation, apoptosis, migration, invasion, metastasis and chemotherapeutic resistance (26)(27)(28)(29). The current study demonstrated that PTPN12 upregulation inhibits the proliferation and invasion of RB cells and that the inhibition of miR-503 directly targets PTPN12, suppressing the progression of RB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTPN12, is a member of the Protein tyrosine phosphatases family (48) and is frequently downregulated in several types of human cancer, including nasopharyngeal carcinoma (28), ovarian cancer (49), breast cancer (50) and hepatocellular carcinoma (51). PTPN12 serves as a tumor-suppressor in cancer initiation and progression by regulating a wide range of biological processes, including cell proliferation, apoptosis, migration, invasion, metastasis and chemotherapeutic resistance (26)(27)(28)(29). The current study demonstrated that PTPN12 upregulation inhibits the proliferation and invasion of RB cells and that the inhibition of miR-503 directly targets PTPN12, suppressing the progression of RB.…”
Section: Discussionmentioning
confidence: 99%
“…3A). PTPN12 has previously been demonstrated to serve as a tumor-suppressant in multiple types of human malignancy, so was selected for additional analysis (26)(27)(28)(29). A luciferase reporter assay was used to verify the prediction that PTPN12 served a role in the expression of miR-503.…”
Section: Ptpn12 Is a Direct Target Gene Of Mir-503 In Rb Cellsmentioning
confidence: 99%
“…On the contrary, the overexpression of PTPN12 (protein tyrosine phosphatase nonreceptor type 12) in NPC cells has decreased EGFR expression. It has enhanced caspase3 activity, preventing the proliferation and invasion of tumor cells [ 80 ]. Overall, the EGFR and EGFR signalling pathways play an essential role in the invasion and metastasis of NPC.…”
Section: The Role Of Egfr Pathways In Nasopharyngeal Carcinomamentioning
confidence: 99%
“…They serve as templates for protein synthesis on ribosomes and determine the amino acid sequences of peptide chains 15,16 . The expression level and methylation of mRNA are closely related to the processes of tumorigenesis, proliferation, and invasion [17][18][19] . In addition, mRNAs are closely associated with the prognoses of various tumors and can be used as reliable biomarkers for prognosis [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%